Task-oriented control of muscle coordination during cycling - Enders, H.; Maurer, C.; Baltich, J.; Nigg, B. M. (Medicine & Science in Sports & Exercise, 2013)
Purpose: This study investigated the effects of different biomechanical constraints on the variability of muscle activation during cycling.